HR Orientation and Employee Performance: The Mediating Role of Affective Climate and Recruitment Efficiency - Firmanshah, Bayu; Sandi Nasrudin Wibow; Siti Fatinnah binti Ab Rahman (Jurnal Bisnis dan Manajemen, 2026)
This study aims to examine the direct and indirect effects of Employee Human Resource Orientation (EHRO) on Employee Performance through Positive Affective Climate and Recruitment Efficiency in a service organization context. Drawing upon Strategic Human Resource Management (SHRM), Affective Events Theory, and Signaling Theory, this research proposes a dual mediation model explaining how strategic HR orientation translates into performance outcomes. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data collected from PT Pos Indonesia (Persero), Cirebon Branch. The findings reveal that EHRO does not significantly influence Employee Performance directly (β = 0.181, p = 0.069). However, EHRO significantly affects Positive Affective Climate (β = 0.503, p < 0.001) and Recruitment Efficiency (β = 0.477, p < 0.001), both of which significantly improve Employee Performance. Mediation analysis confirms full mediation through Positive Affective Climate and significant indirect effects through Recruitment Efficiency, with the affective pathway demonstrating stronger influence. The model explains 54.7% of the variance in Employee Performance. These findings suggest that strategic HR orientation enhances employee performance primarily through emotional and recruitment mechanisms rather than direct intervention. The study contributes to SHRM literature by validating a dual mediation framework in an emerging economy service setting.